Hemodynamics of the VenusP Valve System™—an in vitro study - Chen, Huang; Samaee, Milad; Tree, Michael; Dasi, Lakshmi; Yoganathan, Ajit (Frontiers in Medical Technology, 2024)
This study aims to evaluate the fluid dynamic characteristics of the VenusP Valve System TM under varying cardiac outputs in vitro. A thorough hemodynamic study of the valve under physiological cardiac conditions was conducted and served as an independent assessment of the performance of the valve. Flow fields downstream of the valve near the pulmonary bifurcation were quantitatively studied by two-dimensional Particle Image Velocimetry (PIV). The obtained flow field was analyzed for potential regions of flow stasis and recirculation, and elevated shear stress and turbulence. High-speed en face imaging capturing the leaflet motion provided data for leaflet kinematic modeling. The experimental conditions for PIV studies were in accordance with ISO 5840-1:2021 standard (1), and two valves with different lengths and different orientations were studied.Results show good hemodynamics performance for the tested valves according to ISO 5840 standard without significant regions of flow stasis. Observed shear stress values are all well below established hemolysis limits.